2011
DOI: 10.1063/1.3632052
|View full text |Cite
|
Sign up to set email alerts
|

A molecular Debye-Hückel theory and its applications to electrolyte solutions

Abstract: In this report, a molecular Debye-Hückel theory for ionic fluids is developed. Starting from the macroscopic Maxwell equations for bulk systems, the dispersion relation leads to a generalized Debye-Hückel theory which is related to the dressed ion theory in the static case. Due to the multi-pole structure of dielectric function of ionic fluids, the electric potential around a single ion has a multi-Yukawa form. Given the dielectric function, the multi-Yukawa potential can be determined from our molecular Debye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
119
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(120 citation statements)
references
References 27 publications
1
119
0
Order By: Relevance
“…In our previous study, it is found that the inclusion of several DH modes (typically L = 2 or 4) are capable to predict the thermodynamics of electrolyte solutions or molten salts [25,8,9], and so one can always safely truncate the elements in Eq. (25) to a finite number.…”
Section: A Molecular Debye-hückel Theory Of Electrolyte Solutions Basmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, it is found that the inclusion of several DH modes (typically L = 2 or 4) are capable to predict the thermodynamics of electrolyte solutions or molten salts [25,8,9], and so one can always safely truncate the elements in Eq. (25) to a finite number.…”
Section: A Molecular Debye-hückel Theory Of Electrolyte Solutions Basmentioning
confidence: 99%
“…We consider a restricted primitive model of electrolyte solution and denote ϕ j (r) as the mean electric potential of a single ion j with charge q j and diameter σ. The electric potential ϕ j (r) of the ion is expanded by a set of DH-like modes [25], such that…”
Section: A Molecular Debye-hückel Theory Of Electrolyte Solutions Basmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous theoretical frameworks for aqueous electrolyte solution modelling have been described in the literature; recent examples include the publications of Afanas'ev (2011), Fraenkel (2011, Haghtalab et al (2011), Hsieh and Lin (2011), Hu et al (2011), Lamperski and Pluciennik (2011), Li et al (2011), Partanen (2012), Sun and Dubessy (2012), Tian et al (2012) and Xiao and Song (2011). Of the various approaches proposed none has been more widely adopted than that of Pitzer (1973).…”
Section: Introductionmentioning
confidence: 99%